Measuring Teaching Effectiveness: A comprehensive analysis of assessment tools, criteria, and standardization (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Students' social and attitude development is said to be influenced by effective instructors just as much as their academic performance. "What makes a good teacher?" is an old and well-studied topic. Teacher effectiveness (TE) has been measured using a variety of approaches, each with its own set of advantages and disadvantages. In order to measure how successful school instructors are, many turn to the Teacher Effectiveness Scale (TES-KU) created by Kulsum (2011). The majority of research participants viewed the administration of this 60-item measure as tedious and time-consuming. Therefore, a condensed version of this scale was attempted. The Principle Component technique was used to factor analyze responses from 200 school instructors. It would be ideal if schools and teachers could agree on a common set of criteria to evaluate classroom performance. Also, it would be great if these measures were congruent with what we know about how to evaluate teachers' efficacy in the classroom. Sadly, most institutions are currently not operating at this optimum level. The purpose of this interview research was to gather information from 72 physics teachers on the methods used by their schools to determine the efficacy of their lessons.